South Africa : Financial Sector Assessment Program-Stress Testing the Financial System-Technical Note. (IMF Staff Country Reports; Country Report, 2015)
This Technical Note discusses stress testing (ST) results for the financial system of South Africa. The bank STs suggest that banks have adequate capital to withstand severe shocks, but need larger liquidity capacity to meet regulatory requirements. Even in the severe scenario in which GDP falls for three consecutive years, banks' capital buffers seem sufficient, although the impact of a large default could be significant. Banks also appear resilient to market risks in both the trading and banking books. Some banks, however, would have difficulty meeting the Liquidity Coverage Ratio without the Committed Liquidity Facility of the South African Reserve Bank.